Bis(pentafluorosulfanyl)phenyl Azide as an Expeditious Tool for Click Chemistry toward Antitumor Pharmaceuticals. Issue 5 (3rd March 2014) - Yang, Yu‐Dong; Tokunaga, Etsuko; Akiyama, Hidehiko; Saito, Norimichi; Shibata, Norio
Abstract The inclusion of fluorine in pharmaceutical agents is a well‐ established means of improving their druglike properties. Different substituents have been used to introduce fluorine, including trifluoromethyl and trifluoromethylthio groups; however, the pentafluorosulfanyl remains relatively underutilized although it is considered to be a "super" trifluoromethyl group. Here, a series of pentafluorosulfanyl‐containing 1, 4‐disubstituted‐1, 2, 3‐triazoles were synthesized by click reaction from alkynes and 3, 5‐bis(pentafluorosulfanyl)phenyl azide in excellent yields. Their biological activities were evaluated against human leukemic monocyte lymphoma U937 cells. In particular, 1‐(3, 5‐bis(pentafluorosulfanyl)phenyl)‐4‐(4‐fluorophenyl)‐1H‐1, 2, 3‐triazole exhibited potent efficacy in cell viability assays at a concentration of 60 μM and was shown to activate caspase‐3 activity, indicating induction of apoptosis. An analogous fluorenol‐substituted triazole also exhibited promising cytotoxic effects against U937 cells, with an IC50 value of 6.29 μM. Given these preliminary results, these pentafluorosulfanyl‐containing triazoles represent useful building blocks for the further development of novel antitumor agents.